Analisis Efektivitas Coretax Sebagai Strategi Dalam Peningkatan Penerimaan Pajak Daerah DKI Jakarta - alfirdaus, Naoval; Anas , Syaiful (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research was conducted with the aim of knowing: (1) strategic efforts of the Regional Revenue Agency in overcoming obstacles and expanding coretax integration as an effort to increase local tax revenue; (2) the effectiveness of coretax as a strategy in increasing local taxes in DKI Jakarta province; (3) obstacles experienced by the Regional Revenue Agency in carrying out strategies to increase local taxes through coretax services; and (4) recommendations and steps that need to be taken to increase local tax revenue in DKI Jakarta province in the future. This research method uses a qualitative descriptive method using data collection techniques of interviews, observation and documentation. The results showed that the application of the coretax digital-based service system had a positive impact on local tax revenue, with key factors: (1) increased data accuracy; (2) ease of use for taxpayers; and (3) better system integration. The factors that hinder in carrying out the strategy of increasing local tax revenue through coretax are unstable server disruptions, system services that are not fully integrated, and lack of understanding of technology among tax officials.